2014
DOI: 10.1179/1743132814y.0000000331
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety assessment of alteplase in the treatment of stroke — gender differences

Abstract: The use of alteplase in women during the treatment of stroke is associated with a greater and faster improvement in their neurological state in comparison with men. Treating stroke with alteplase in women improves long-term prognosis regarding self-efficacy in everyday functioning. Finally, there are no gender-related differences regarding the safety of intravenous thrombolytic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…Overall, 1,685 studies were identified and screened for retrieval from the analyzed databases. Careful selection based on the criteria described above identified the following 16 reports involving 60,159 patients as being suitable for inclusion in the meta-analysis: Spaander et al, 31 Buijs et al, 30 Hametner et al, 32 Al-hussain et al, 33 Lasek-Bal et al, 34 Nathanson et al, 35 Lorenzano et al, 23 Martinez-Sanchez et al, 29 Forster et al, 25 Jovanovic et al, 36 Meseguer et al, 26 Kent et al, 22 Gomez-Choco et al, 37 Arnold et al, 27 Elkind et al, 28 Hill et al 24 The flowchart for these studies is shown in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 1,685 studies were identified and screened for retrieval from the analyzed databases. Careful selection based on the criteria described above identified the following 16 reports involving 60,159 patients as being suitable for inclusion in the meta-analysis: Spaander et al, 31 Buijs et al, 30 Hametner et al, 32 Al-hussain et al, 33 Lasek-Bal et al, 34 Nathanson et al, 35 Lorenzano et al, 23 Martinez-Sanchez et al, 29 Forster et al, 25 Jovanovic et al, 36 Meseguer et al, 26 Kent et al, 22 Gomez-Choco et al, 37 Arnold et al, 27 Elkind et al, 28 Hill et al 24 The flowchart for these studies is shown in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 40 sICH was not defined in the reports for the remaining studies. 25 27 33 34 The detailed individual characteristics of the studies are tabulated in Table 1 , while particularly interesting outcomes obtained in the meta-analysis are listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…However, a better understanding of the drivers of sex differences in rt-PA treatment is needed to maximize the population benefit of developing systems of care and eliminate existing disparities. Identification of these drivers is of particular importance considering the evidence that rt-PA is associated with a greater improvement in stroke symptoms for women than for men, with no differences in adverse events after rt-PA administration between men and women ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous thrombolysis is the mainstay of management of acute ischemic stroke [15]. Importantly, women who suffer an acute ischemic stroke appear to respond better to intravenous thrombolysis than men [16,17]. Despite these differences and the more adverse outcome of women after stroke, several studies showed that women are less likely to receive intravenous thrombolysis than men [18,19].…”
Section: Management Of Acute Stroke In Men and Womenmentioning
confidence: 99%